THE EFFECT OF SALINITY, TEMPERATURE AND GAMETE DENSITY ON THE EMBRYONIC DEVELOPMENT OF THE SLIPPER OYSTER, CRASSOSTREA IREDALEI FAUSTINO - Achmad Sudradjat (Indonesian Fisheries Research Journal, 1996)
The study was designed to investigate effects of temperature, salinity and gamete density in the percentage of ernbryos that develop into normal D-larvae of Crassostrea iredalei 30 h after fertilization.